Litigation for health technology accessibility: A tool for inequality? Reflections based on case study analysis - Marin, Gustavo Horacio (2020)
INTRODUCTION: The objective of this work is to analyze the characteristics of litigation for access to health’s goods and services in the Social Health Insurance (SHI) of Buenos Aires, Argentina. METHOD: Descriptive study with analytical stage, performed in SHI, analyzing litigation done by beneficiaries along 15-years period to obtain goods or service from health managers. Variables explored were: Reason for litigation, delay time in case resolution, final result of judicial sentence, judges, lawyers and intervening professionals, income level of beneficiaries who started the litigation. RESULT: 825 cases were analyzed during the study period according the method described. Demands increased 29.2 ±% per year. Medicines were the goods that most requested legal protection resources (32.5%). 51.9% of these litigations were due to medicines that have less than 24 months of registration by the National Regulatory Agency. The average delay for the final resolution of the procedure was 3.7 months. Judge's sentence was favorable to the beneficiaries in 97.4%. Although there are 27 judicial departments and many courts in each one; cases were concentrated in 47.4% only 2 very few courts. Litigation cases promoted by 112 out of the 15000 doctors that provides services to the SHI. In 73.7% of the cases, beneficiaries that litigated had a salary that exceed 4 times the minimum wage, and only 3.2% of them had low income. CONCLUSION: We show how legal appeals might be working as an inverse strategy to the one desired, transferring collective resources belonging to the entire population, towards an specific demand from the most economically wealthy sector of society. As long as access to health care litigation maintains its current individualistic pattern, it will hardly be able to develop its full potential to guarantee effective respect for the collective right to access to goods that beneficiary the whole community.